Makna Eksoteris dan Esoteris Agama dalam Sikap Keberagamaan Eksklusif dan Inklusif - Kunawi Basyir (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
Within the last decades, known to us as the century of spirituality, the world civilization has been murkily colored by the darkness, and it has been caused by our sharp different view when we try to understand the meaning of religion, including Islam. This has led to the absence of “a bowl” of peace, justice, and equality for every person to freely express their socio-religious activities. For instance, to the exclusivists, Islam is blindly viewed as the sole religion that possesses the absolute value of truth (absolutism). Consequently, this group sees that other religions possess no truth and, therefore, they must be obliterated. This group sees islām as a term to reject religious pluralism in Indonesia. On the other side, the inclusivists consider the truth of islām as the universal truth. In this regard, they argue that Islam’s truth as a religion is the sole truth, but the truth of islām cannot be monopolized only by a certain religion. They further argue that other religions may also possess the truth of islām. Paying close attention to such a different understanding of islām, this article attempts to re-read and re-analyze it from a socio-cultural approach (or strictly speaking from a philosophical and theological point of view).